La narrazione storica nei videogiochi: il caso di Sid Meier’s Civilization - Laboratorio LAPSUS (Diacronie. Studi di Storia Contemporanea, 2021)
The receptivity of the concepts and messages embedded in video games, as well as their use in education, have already been investigated in various social science disciplines. However, the video game medium still suffers from a lack of consideration by historians and struggles to establish itself as a real object of investigation, even though there are many titles dealing with historical themes. In this unguarded margin, stereotypes, historical fallacies and distorted narratives have potential space to proliferate. The paper aims to analyse the legacies and imaginaries of Sid Meier’s Civilization saga, considered one of the most famous history-themed strategy video games in the world.